2005
DOI: 10.7202/705502ar
|View full text |Cite
|
Sign up to set email alerts
|

Mécanismes d'élimination de l'azote et du phosphore dans un chenal algal à haut rendement

Abstract: Le devenir de l'azote(N) et du phosphore (P) a été étudié dans un chenal à haut rendement (CAHR) au cours de la période d'adaptation puis en phase stationnaire. En moyenne, la part de N total perdue atteint 34,5% du N admis en période d'adaptation et 24,5% en phase stationnaire tandis que la part assimilée par les algues atteint respectivement 32 et 43,5%. L'azote organique particulaire s'accumule dans le sédiment et subit une minéralisation lente pendant la phase d'adaptation puis rapide en phase stationnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Many authors showed the influence of abiotic physico-chemical parameters on the dynamics of nutrients in the water. Thus, according to Hafiane et al [36], hot weather leads to increased net loss of nitrogen as NH 3 . In the same way, Dovonou et al [37] prove that because NH 4 + proceed from the decomposition of excreta, it pass to gas form and lead to an elevation of pH.…”
Section: Correlations Between Parameters Measured In Situ and Nutrienmentioning
confidence: 99%
“…Many authors showed the influence of abiotic physico-chemical parameters on the dynamics of nutrients in the water. Thus, according to Hafiane et al [36], hot weather leads to increased net loss of nitrogen as NH 3 . In the same way, Dovonou et al [37] prove that because NH 4 + proceed from the decomposition of excreta, it pass to gas form and lead to an elevation of pH.…”
Section: Correlations Between Parameters Measured In Situ and Nutrienmentioning
confidence: 99%
“…Nitrogen, mainly in the form of ammonia, is rapidly converted into nitrite (NO 2 − ) and nitrate (NO 3 − ) after oxidation in the presence of heterotrophic bacteria [25]. These bacteria require an anoxic environment and a carbon source to carry out the denitrification process.…”
Section: Physico-chemical and Bacteriological Parametersmentioning
confidence: 99%
“…Le premier facteur peut être assimilé à une décantation qui dépend essentiellement de la taille des MES (EL HAFIANE et al, 2003). Dans le cas de cette étude et grâce aux systèmes d'agitation utilisés, l'impact de ce facteur sur les performances d'élimination du phosphore dans le CAHR est minime.…”
Section: Nutrimentsunclassified